2016
DOI: 10.1186/s13195-016-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral glucose metabolism after 3 weeks of noninvasive electrical stimulation of mild cognitive impairment patients

Abstract: BackgroundMild cognitive impairment (MCI) is a syndrome that disrupts an individual’s cognitive function but preserves activities of daily living. MCI is thought to be a prodromal stage of dementia, which disrupts patients’ daily lives and causes severe cognitive dysfunction. Although extensive clinical trials have attempted to slow or stop the MCI to dementia conversion, the results have been largely unsuccessful. The purpose of this study was to determine whether noninvasive electrical stimulation of MCI cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 53 publications
7
86
3
Order By: Relevance
“…As far as receptor PET is concerned, we are aware of one study investigating acute effects on the μ-opioid receptor selective radioligand [ 11 C]carfentanil giving preliminary evidence that the opioid system might be engaged by tDCS but no direct comparison between active and placebo tDCS were reported (DosSantos et al 2012). A similar study using tDCS showed increased glucose metabolism in the temporal cortex (Yun et al 2016). Here nine tDCS treatments at 2 mA over a period of three weeks in 16 patients with mild cognitive impairment and identical electrode Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as receptor PET is concerned, we are aware of one study investigating acute effects on the μ-opioid receptor selective radioligand [ 11 C]carfentanil giving preliminary evidence that the opioid system might be engaged by tDCS but no direct comparison between active and placebo tDCS were reported (DosSantos et al 2012). A similar study using tDCS showed increased glucose metabolism in the temporal cortex (Yun et al 2016). Here nine tDCS treatments at 2 mA over a period of three weeks in 16 patients with mild cognitive impairment and identical electrode Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we tested the impact of tDCS at three different stimulation strengths in a continuous infusion [ 18 F]FDG-study. Based on close connections between glutamate and the [ 18 F]FDG-signal, a previous positive MRS-result (Hone-Blanchet et al 2016) and increases of repetitive tDCS treatments on [ 18 F]FDG with identical electrode positioning (Yun et al 2016), we hypothesized to detect increases of glucose consumption during tDCS in the dlPFC and connected brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…One RCT randomized 16 patients with MCI to active or sham tDCS . Active tDCS was delivered with an anode at the left DLPFC and a cathode at the right DLPFC, at 2 mA for 20 minutes, 3 days a week, for 3 weeks.…”
Section: Tdcs In Admentioning
confidence: 99%
“…One RCT randomized 16 patients with MCI to active or sham tDCS. 25 Active tDCS was delivered with an anode at the left DLPFC and a cathode at the right DLPFC, at 2 mA for 20 minutes, 3 days a week, for 3 weeks. Cognitive assessment and 18 F-fluoro-2-deoxyglucose positron emission tomography were administered at baseline and the end of the tDCS course.…”
Section: Transcranial Magnetic and Electrical Stimulation In Alzheimementioning
confidence: 99%
“…Functional neuroimaging such as single photon emission computed tomography (SPECT) or positron emission tomography (PET) may be useful for evaluating brain changes induced by tDCS. For example, previous studies found that glucose metabolism was increased in several brain regions besides the target region following tDCS in patients with mild cognitive impairment and Alzheimer's disease . Therefore, this pilot study was conducted to investigate the effects of tDCS on motor symptoms and regional cerebral blood flow (rCBF) in PD patients using technetium‐99m ethyl cysteinate dimer (Tc‐99m ECD) SPECT.…”
Section: Introductionmentioning
confidence: 99%